Functionalized alkenyl side chains: a feasible strategy to improve charge transport and photovoltaic performance. Issue 6 (15th January 2020) - Zheng, Bing; Liu, Juan; Pan, Xuexue; Zhang, Yu; Wang, Zaiyu; Liu, Feng; Wan, Meixiu; Huo, Lijun
Abstract : To pursue effective charge transport and high fill factor (FF) in photovoltaic devices, adopting ordered polymers with enhanced hole mobility is greatly desired. Abstract : To pursue effective charge transport and high fill factor (FF) in photovoltaic devices, adopting ordered polymers with enhanced hole mobility is greatly desired. Currently, a popular strategy in improving charge transport has been applied by enforcing the coplanarity of fused-ring conjugated structures. However, their synthetic complexity hinders their further development. Here, we successfully developed an effective strategy to introduce soluble alkenyl side chains in D–A type photovoltaic polymer backbones to improve the charge transport ability and photovoltaic performance. The introduction of the trans -vinylene (CHCH) linkage in alkenyl side chains strengthens the polymeric crystalline properties and charge transport ability, and further improves the photovoltaic performance. Meanwhile, a high FF of 0.73 can still be obtained for a device with a film thickness of 200 nm. The low cost, feasible chemical strategy could potentially be applied for other thickness-insensitive organic photovoltaic materials design.